Implementasi Model Gamifikasi dalam Pembelajaran Fikih untuk Meningkatkan Hasil Belajar Siswa Kelas 8 MTs Ma’arif Balong Ponorogo - Umami, Halida; Al-Muljahidin; Azizah, Nurul; Mufidah, Zuhrotul (STAI Ali bin Abi Thalib Surabaya, 2025)
This study investigates the implementation of gamified learning strategies to enhance student engagement and academic achievement in the Fiqh subject among eighth-grade students at MTs Ma’arif Balong, Ponorogo. Preliminary observations revealed that 59% of students did not meet the Minimum Mastery Criteria (MMC), largely due to the predominant use of traditional lecture-based instruction, which limited active student participation and resulted in poor content comprehension. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, utilizing a descriptive qualitative approach. The participants consisted of 22 students, and data were collected through observation, testing, documentation, and interviews. Data analysis included assessments of test scores, learning outcomes, and student engagement throughout the instructional process. The results indicate a significant improvement in student learning outcomes, rising from 36.36% in Cycle I to 90.91% in Cycle II. Student engagement similarly increased from 49.15% to 86.65%. These findings suggest that gamification is an effective pedagogical approach for improving both student participation and academic performance in Fiqh instruction. It is recommended that educators adopt this method consistently and explore its application in other subject areas.